PERAN RASIO LIKUIDITAS DAN SOLVABILITAS SEBAGAI DETERMINAN KINERJA KEUANGAN PADA PT. KIMIA FARMA TBK - Tri Sulistyani; Lisdawati Lisdawati (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to analyze the role of liquidity and solvency ratios in determining the financial performance of PT. Kimia Farma Tbk, both partially and simultaneously. This research employs a quantitative approach with an associative research design. The data used are secondary data obtained from the company’s financial statements over the period 2016–2025. The data analysis technique applied is multiple linear regression, supported by classical assumption tests, correlation analysis, coefficient of determination, and partial and simultaneous significance testsThe results show that the liquidity ratio, measured by the current ratio, has a positive and significant effect on financial performance as measured by return on assets. This indicates that the better the company’s ability to meet its short-term obligations, the more optimal its financial performance. Meanwhile, the solvency ratio, measured by the debt to equity ratio, does not have a significant effect on return on assets, indicating that debt-based capital structure does not necessarily improve profitability. Simultaneously, liquidity and solvency ratios have a significant effect on financial performance, implying that both variables still play an important role in explaining variations in the financial performance of PT. Kimia Farma Tbk.